Direct observation of coherent elastic antineutrino–nucleus scattering - N. Ackermann; H. Bonet; A. Bonhomme; C. Buck; K. Fülber; J. Hakenmüller; J. Hempfling; G. Heusser; M. Lindner; W. Maneschg; K. Ni; M. Rank; et al. (Nature, 2025)
Abstract Neutrinos are elementary particles that interact only very weakly with matter. Neutrino experiments are, therefore, usually big, with masses in the multi-tonne range. The thresholdless interaction of coherent elastic scattering of neutrinos on atomic nuclei leads to greatly enhanced interaction rates, which allows for much smaller detectors. The study of this process gives insights into physics beyond the Standard Model of particle physics. The CONUS+ experiment1 was designed to first detect elastic neutrino–nucleus scattering in the fully coherent regime with low-energy neutrinos produced in nuclear reactors. For this purpose, semiconductor detectors based on high-purity germanium crystals with extremely low-energy thresholds were developed2. Here we report the first observation of a neutrino signal with a statistical significance of 3.7σ from the CONUS+ experiment, operated at the nuclear power plant in Leibstadt, Switzerland. In 119 days of reactor operation (395 ± 106) neutrinos were measured compared with a predicted number from calculations assuming Standard Model physics of (347 ± 59) events. With increased precision, there is potential for fundamental discoveries in the future. The CONUS+ results in combination with other measurements of this interaction channel might therefore mark a starting point for a new era in neutrino physics.